Evaluating Board Composition, Diversity, and Governance in National Sport Federations: Assessing the Impact of Board Size in the Netherlands - Asten Dissel, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study provides a comprehensive analysis of board characteristics in the National Sports Federation of the Netherlands. The Netherlands has implemented regulations to promote board diversity, emphasising the importance of ensuring diverse representation. This study utilises a cross-sectional and descriptive research design, employing content analysis of publicly accessible data. The study's findings indicate an increasing presence of women in leadership roles, specifically on boards and in managerial positions, within sports organisations. There is a growing emphasis on gender-balanced boards as a means to enhance governance and decision-making through the inclusion of diverse perspectives. The study conducted a comparative analysis of the Netherlands in relation to other countries in order to enhance the argument. The study contributes to the existing theoretical literature on board diversity and governance in sports organisations. The study emphasises the importance of sports organisations developing policies that prioritise diversity and inclusivity, involving all relevant stakeholders in the governance processes.